Antimicrobial activity of mangrove plant AcrostichumSpeciosum - Saad, Shahbudin; Bakhtiar, M. Taher; Darnis, Deny Susanti; Qaralleh, Haitham; Noorhaidi, Nooradila; Awang, Anis Fadhlina Izyani (Journal of Pure and Applied Microbiology, 2013)
The antimicrobial activity of leaves, stem and root of Acrostichumspeciosumwas evaluatedusing different polarity extraction solvents namely n-hexane, ethyl-acetate and methanol.The samples were tested by disc diffusion and microdilution method against sixmicroorganisms after the extraction process for their antimicrobial activity. All extracts tested in disc diffusion test showed no antimicrobial activity. The exception of this is the moderate antibacterial activity of the ethyl-acetate root extracts against the Gram-positive strains (Bacillus cereus) and the Gram-negative bacterium Escherichia coli. Ethyl-acetate root extracts appeared to have bacteriostatic and bactericidal action against B. cereus at the concentration equal to 0.04 mg/mL (MIC=MBC) while it has bacteriostatic action against E. coli at the concentration equal to 0.012 mg/mL.The inhibition of microbial growth at concentration as low as 0.04 mg/mL indicated the potent antimicrobial activity of ethyl-acetate root extracts of A. speciosum.